Cysticercosis-Related Hospitalizations in the United States, 1998–2011 - O'Keefe, Kaitlin A. (Am J Trop Med Hyg, 2015)
Cysticercosis has become increasingly recognized as an important infection in the United States in recent decades. Despite its potential impact, there is a lack of comprehensive information on the nationwide burden of disease. To better define the burden of cysticercosis in the United States, we analyzed in-patient records using the Nationwide Inpatient Sample for 1998–2011 to estimate cysticercosis-related hospitalizations and patient/institutional characteristics. There were an estimated 33,060 (95% confidence interval [95% CI] = 29,610.5–36,510.3) cysticercosis-related hospitalizations nationwide, representing a hospitalization rate of 8.03 per million population. The highest proportion of cases were male (54.8%), Hispanic (62.0%), aged 18–44 (58.8%), and occurred in the West (45.1%). An estimated 459 deaths occurred, representing an in-hospital case-fatality rate of 1.4%. These findings indicate the burden of cysticercosis-related hospitalizations in the United States is considerable and may be greater than currently appreciated. Cysticercosis should be a nationally reportable disease.